The subspecific characters and distribution of the new world skimmers - rynchops nigra (1944)
The distribution of the forms of the New World rayador, or skimmer, Rynchops nigra, and the characters that mark the geographic races, have been matters of interest to me for a number of years, an interest heightened by recent discussions in current literature of the identity of the birds found on the Pacific coast of Mexico, and far to the south in Chile. Investigation into these matters with the material available in the National Museum not being conclusive, specimens from Mexico and the West Indies southward to Argentina and Chile in other large collections in the United states have been assembled through the courtesy of Dr. Robert Cushman Murphy of the American Museum of Natural History, James l.. Peters of the Museum of Comparative Zoology,W. E. C. Todd of the Carnegie Museum, and Dr. Karl P. Schmidt of the Field Museum of Natural History. I have also to thank Dr. Alden H. Miller for the use of one specimen from Chubut in the Museum of Vertebrate Zoology, and Dean Amadon for certain notes on this group of birds that he had assembled.